Against the Darkness : The doctrine of angels, satan, and demons. - Cole, Graham A. (Crossway, 2019)
Many Christians live as though they are effectively alone. However, there is another realm of intelligent life that plays a role in the world―angelic beings. This book explores the doctrine of angels and demons, answering key questions about their nature and the implications for Christians’ beliefs and behavior, helping readers see their place in the larger biblical plotline that includes supernatural beings. An understanding of the reality of angels and demons encourages believers to be vigilant in the light of spiritual warfare and to be confident in Christ’s victory on the cross.